APPLICATION OF PROBLEM BASED LEARNING TO REDUCE MISCONCEPTIONS OF THE CONCEPT OF HEROES IN GRADE V STUDENTS OF SDN TEMANGGAL MAGELANG - Nur Aiman; Dhiniaty Gularso (Universitas Majalengka, 2026)
This research aims to overcome the misunderstanding of elementary school students in social studies learning, especially in the concept of heroes who tend to be understood narrowly as figures of the independence period who have passed away. This condition shows the need for a learning approach that is able to facilitate the development of deeper and meaningful conceptual understanding. This study aims to describe the application of the Problem Based Learning (PBL) model in reducing misunderstandings of the concept of heroes and analyze changes in students' understanding after participating in problem-based learning. This study uses a qualitative case study method involving grade V students of SDN Temanggal. The learning process is designed through PBL stages which include problem orientation, information exploration, group discussions, and digital project development with the theme